2019
DOI: 10.1016/j.carrev.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Network Meta-Analysis of Percutaneous Intervention-Based Revascularization Strategies for ST-Elevation Myocardial Infarction and Concomitant Multi-Vessel Disease

Abstract: In this NMA, CR-I was associated with reduction in all-cause mortality and re- infarction compared with IRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Previous network meta-analysis conducted by Bangalore et al showed that immediate complete revascularization might be the preferred strategy in patients with STEMI and multivessel disease due to the significantly reduced risks of all-cause death or MI, all-cause death, MI and repeat revascularization, whereas staged complete revascularization only reduced the risk of repeat revascularization, but did not reduce the risk of all-cause death or MI compared with culprit-only PCI (16). Similarly, another network meta-analysis also indicated that immediate complete revascularization was associated with reduction in all-cause mortality and MI compared with culpritonly PCI, while no difference was found between staged complete revascularization and culprit-only PCI for all the endpoints except repeat revascularization (17). In contrast, some network meta-analyses concluded that staged rather than immediate complete revascularization was the best strategy for improving survival in patients with STEMI and multivessel disease (4,29).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous network meta-analysis conducted by Bangalore et al showed that immediate complete revascularization might be the preferred strategy in patients with STEMI and multivessel disease due to the significantly reduced risks of all-cause death or MI, all-cause death, MI and repeat revascularization, whereas staged complete revascularization only reduced the risk of repeat revascularization, but did not reduce the risk of all-cause death or MI compared with culprit-only PCI (16). Similarly, another network meta-analysis also indicated that immediate complete revascularization was associated with reduction in all-cause mortality and MI compared with culpritonly PCI, while no difference was found between staged complete revascularization and culprit-only PCI for all the endpoints except repeat revascularization (17). In contrast, some network meta-analyses concluded that staged rather than immediate complete revascularization was the best strategy for improving survival in patients with STEMI and multivessel disease (4,29).…”
Section: Discussionmentioning
confidence: 98%
“…Previous network meta-analyses showed that immediate complete revascularization might be the preferred strategy in this population due to the reduced risks of death or MI, death, MI and repeat revascularization. In contrast, staged complete revascularization did not significantly reduce death or MI compared with culprit-only PCI (16,17). Encouragingly, however, the Complete vs. Culprit-Only Revascularization Strategies to Treat Multivessel Disease after Early PCI for STEMI (COMPLETE) trial showed that staged PCI of non-culprit vessels reduced the 3-year risk of cardiovascular death or MI than culprit-only PCI (18).…”
Section: Introductionmentioning
confidence: 98%
“…The SMILE trial involving NSTEMI patients with MVD showed the superiority of immediate non-IRA PCI compared to multistage PCI in terms of MACCE [22]. However, there are meta-analyses involving trials as well as observational studies showed superiority [23][24][25], non-inferiority [26,27], and inferiority [9] of immediate non-IRA PCI compared with staged PCI in regards to MACCE or all-cause mortality in AMI patients with MVD. A recently published trial, MULTISTARS AMI trial involving acute STEMI patients showed that immediate non-culprit coronary artery PCI is non-inferior compared with staged multivessel PCI in terms of the MACCE, all-cause death, MI, stroke, unplanned ischemia-driven revascularization, or hospitalization for heart failure during the follow-up period.…”
Section: Introductionmentioning
confidence: 99%